2015
DOI: 10.1016/j.conbuildmat.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study about the effects of granular skeleton distribution on the mechanical properties of self-compacting concrete (SCC)

Abstract: In recent years, the use of self-compacting concrete (SCC) has been increasing. Although methods for designing the mixture proportions usually derive from experience with conventional concretes, some specific procedures still are not universally accepted. The design and characterization of SCC influences not only the mix components (paste volume and nature, binder amount and type, granular skeleton, etc.) but also the testing methods used to validate the self-compactability (usually in terms of fluidity, visco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 11 publications
1
6
0
3
Order By: Relevance
“…The failure mode remains fragile for a small amount of wollastonite ( 0.6 M70W30) and becomes ductile with a higher amount ( 0.6 M45W55). This might be explained by the modification of the granular skeleton by the micrometric acicular wollastonite [23], and by the modification of the geopolymer network, as previously seen with FTIR spectroscopy and thermal measurements. The addition of glass fibers in the 0.6 M geopolymer ( 0.6 M90G10) leads to a decrease in both the compressive strength by 56% and in the slope of the elastic regime (Young modulus).…”
Section: ) Microstructure and Mechanical Properties Of The Geopolymer Compositessupporting
confidence: 53%
See 1 more Smart Citation
“…The failure mode remains fragile for a small amount of wollastonite ( 0.6 M70W30) and becomes ductile with a higher amount ( 0.6 M45W55). This might be explained by the modification of the granular skeleton by the micrometric acicular wollastonite [23], and by the modification of the geopolymer network, as previously seen with FTIR spectroscopy and thermal measurements. The addition of glass fibers in the 0.6 M geopolymer ( 0.6 M90G10) leads to a decrease in both the compressive strength by 56% and in the slope of the elastic regime (Young modulus).…”
Section: ) Microstructure and Mechanical Properties Of The Geopolymer Compositessupporting
confidence: 53%
“…Moreover, introducing those reinforcement elements modifies the granular skeleton of the material. Santos et al [23] have indeed demonstrated that a continuous granular skeleton leads to a better compressive strength in the case of self-compacting concrete. Short fibers (length < 20 mm) are the most commonly used reinforcement elements for castable materials, as they can be easily mixed and casted within the geopolymer matrix.…”
Section: Introductionmentioning
confidence: 95%
“…In 1990, Shilstone [18] developed design charts to optimize the particle size distribution of the aggregate to lower the paste volume needed to fill the voids. In 2015, Santos et al [19] used two aggregates with different particle size distributions in the production of SCC and showed that the particle size distribution has great effects on the performance of SCC. In same year, Lindquist et al [20] blended three aggregates with distinct sizes to form a 'haystack distribution' to minimize the voids in the aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…By increasing the volume of fine aggregates, the need for hard particle surface area and water increases, the friction between the coarse aggregates decreases, therefore the shear stresses are increased and the plastic viscosity is reduced. It was also concluded that the larger the size of maximum particles, the smaller the specific surface area and less mortar (cement paste) is required to cover the aggregates, and at the same time the smaller the values of rheological properties of the concrete mix, the less dilatation (increase of mixture viscosity while shear stresses increase) is expressed in mixture (Santos et al 2015).…”
Section: Introductionmentioning
confidence: 99%